The Ties That Bind: University Nostalgia Fosters Relational and Collective University Engagement - Green, Jeffrey D.; Cairo, Athena H.; Wildschut, Tim; Sedikides, Constantine (Frontiers in Psychology, 2021)
Does nostalgia for one’s time at university predict current intentions to engage with the university? In Study 1, US participants’ nostalgia for their university experience (university nostalgia) at a southern public university predicted stronger intentions to socialize with fellow alumni, attend a future reunion, volunteer for their university, and donate money to their university. Study 2 replicated these findings with alumni from a northeastern private university, and extended them by finding that the links between university nostalgia and university engagement emerged even when controlling for the positivity of university experience. In both studies, feelings of university belonging mediated most of the associations between university nostalgia and university engagement. In Study 2, the positivity of the university experience moderated the relation between university nostalgia and two indices of university engagement. Specifically, university nostalgia was more strongly associated with intentions to attend a reunion and donate money among those who had a relatively negative university experience. Nostalgia for one’s university past predicts future engagement with the university as well as its members.